INTEGRASI BUDAYA PASIEN DALAM PEMAHAMAN PENYAKIT DAN PENGOBATAN: PERSPEKTIF HADIS DAN IMPLIKASINYA TERHADAP PELAYANAN KESEHATAN - Opi Irawansah; Widyoningsih (Adisam Publisher, 2026)
This study aims to examine the integration of patient culture in understanding illness and treatment from a Hadith perspective and its implications for healthcare services. Using a qualitative approach and a library research method, this study analyzes various scientific literature, including Scopus-indexed journal articles, books on medical anthropology and cultural competence in healthcare, and Islamic sources, particularly Hadith related to health, illness, and treatment. The findings indicate that patient culture significantly influences illness perception, treatment choices, and adherence to medical therapy. In Muslim societies, understanding of illness is not solely based on biomedical explanations but is also shaped by religious beliefs, spiritual values, and traditional practices. The Hadith perspective reinforces the idea that illness is a test and that treatment is a form of effort (ikhtiar), thereby encouraging a balance between medical intervention and spiritual practices. Furthermore, the study reveals a gap between modern medical approaches and patient cultural beliefs, which may lead to miscommunication, low treatment adherence, and reduced quality of healthcare services. The concept of cultural competence is identified as a crucial approach to bridging this gap by integrating patients’ cultural and religious values into clinical practice. This study proposes a holistic healthcare model that combines three dimensions: medical (evidence-based treatment), cultural (patient beliefs and traditions), and spiritual (Hadith-based ethical values). The novelty of this research lies in integrating Hadith perspectives into the discourse of cultural competence in healthcare, which has been predominantly dominated by secular approaches. The study contributes theoretically by enriching interdisciplinary research between health sciences and Islamic studies, and practically by providing insights for developing culturally sensitive, value-based healthcare policies. The findings highlight the urgency of transforming healthcare systems into more inclusive, humanistic, and culturally responsive services.